2004
DOI: 10.1108/10662240410542652
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of online banking: an extension of the technology acceptance model

Abstract: Advances in electronic banking technology have created novel ways of handling daily banking affairs, especially via the online banking channel. The acceptance of online banking services has been rapid in many parts of the world, and in the leading e‐banking countries the number of e‐banking contracts has exceeded 50 percent. Investigates online banking acceptance in the light of the traditional technology acceptance model (TAM), which is leveraged into the online environment. On the basis of a focus group inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

91
984
13
62

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,198 publications
(1,150 citation statements)
references
References 48 publications
91
984
13
62
Order By: Relevance
“…Phatthana and Mat (2010) revealed that perceived ease of use was found to be positively related to e-purchase intention (β=0.39, p= 0.03). This result is consistent with (Davis, 1989;Venkatesh & Davis, 2000;Venkatesh et al, 2003;Pikkarainen et al, 2004;Ramayah & Fernando, 2009;Amin, 2007). The result from the analysis found that PQ significantly related to good governance (β= .147, p= 0.005) which is in line with Colesca and Liliana (2009) where perceived quality is statistically significant to e-government (β= 0.34, p= 0.000).…”
Section: Findings and Discussionsupporting
confidence: 82%
“…Phatthana and Mat (2010) revealed that perceived ease of use was found to be positively related to e-purchase intention (β=0.39, p= 0.03). This result is consistent with (Davis, 1989;Venkatesh & Davis, 2000;Venkatesh et al, 2003;Pikkarainen et al, 2004;Ramayah & Fernando, 2009;Amin, 2007). The result from the analysis found that PQ significantly related to good governance (β= .147, p= 0.005) which is in line with Colesca and Liliana (2009) where perceived quality is statistically significant to e-government (β= 0.34, p= 0.000).…”
Section: Findings and Discussionsupporting
confidence: 82%
“…2,71 -75 Technology is perceived by companies as a strategy that enables them to differentiate themselves from the competitors 76 and facilitates in improving their relationships with consumers. 77 Online banking has gained importance in the last few decades 10 as it makes banking convenient to the consumers. 9 Liao et al 78 in their study on online banking have suggested attributes like ease of use, image, compatibility, willingness and opportunity to explore online banking as factors encouraging online transactions.…”
Section: Online Banking Functional Attributesmentioning
confidence: 99%
“…The online banking behaviour is infl uenced by attributes like ease of use, security, privacy, usefulness, amount of information and perceived enjoyment. 10 This article focuses on the issue of online banking in India, which is considered one of the top emerging markets in the world. Although the western world is familiar with online banking, Indian consumers are still wary of this method of doing banking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bank customers have a lack of trust, lack of controllability, security issue, and concern privacy of electronic banking (Susanto, 2016;Kim, Shin, and Lee, 2009;Lee and Chung, 2009;Luarn and Lin, 2005).Therefore, there are many banking customers that still prefer ATM banking services (Shih and Fang, 2006).Mobile banking firms should emphasize the importance of security, safety, reliability and convenience (Lin, 2011).However, banking firms offer mobile banking service that not only build a safe transaction environment, but also focus on the security of personal information collection and privacy mechanism. Previous studies only discussed the trust perceived and intention of usage mobile banking (Gumussoy, 2016;Gu, Lee, and Suh, 2009) or the concern privacy and personal perceived of adopt Internet banking (Susanto, 2016;Pikkarainen, Pikkarainen, Karjaluoto, and Pahnila, 2004).Few studies have focused on the issue of privacy mechanism influence concerns for personal information, trust perceived, and risk perceived attitude.…”
Section: Introductionmentioning
confidence: 99%